2016
DOI: 10.1111/dmcn.13354
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation tools of dysphagia in children with neuromuscular diseases: a systematic review

Abstract: We did not identify any superior validated tools, either for screening or for evaluation of dysphagia, and no widely accepted protocol. Further studies are needed to identify the simplest assessment with the best psychometric properties for pNMD. We recommend establishing a specific tool for pNMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…A recent systematic review of dysphagia in children focused primarily on boys with DMD; there was a lack of widely accepted screening or evaluation protocol for other pediatric neuromuscular disorders. 61 Boys with DMD were found to have progressive involvement of the oropharyngeal muscles, necessitating the modification of feeding strategies to minimize dysphagia. 62 As transporting and swallowing requires the use of more than 25 pairs of oral and masticatory muscles that are difficult to be assessed by EMG, van den Engel-Hoek et al 63 proposed to use muscle ultrasound as a standard diagnostic tool for the assessment of dysphagia ( Figures 8A-8B), based on their extensive experience with ultrasound in the neuromuscular population.…”
Section: Assessing Muscles That Cannot Be Easily Accessed With Emgmentioning
confidence: 99%
“…A recent systematic review of dysphagia in children focused primarily on boys with DMD; there was a lack of widely accepted screening or evaluation protocol for other pediatric neuromuscular disorders. 61 Boys with DMD were found to have progressive involvement of the oropharyngeal muscles, necessitating the modification of feeding strategies to minimize dysphagia. 62 As transporting and swallowing requires the use of more than 25 pairs of oral and masticatory muscles that are difficult to be assessed by EMG, van den Engel-Hoek et al 63 proposed to use muscle ultrasound as a standard diagnostic tool for the assessment of dysphagia ( Figures 8A-8B), based on their extensive experience with ultrasound in the neuromuscular population.…”
Section: Assessing Muscles That Cannot Be Easily Accessed With Emgmentioning
confidence: 99%
“…Swallowing difficulty is frequently encountered, especially in children with underlying diseases. According to previous studies, swallowing disorders have been reported in 43%–100% of children with cerebral palsy [ 1 2 ] and 35%–80% of children with neuromuscular disease [ 3 ]. Swallowing difficulty may lead to life-threatening conditions, such as aspiration pneumonia (AP), asphyxia, and sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The patients usually develop with motor gain, however, scoliosis, respiratory and bulbar involvement commonly appear in the first decade [3] . Bulbar weakness is found ubiquitously throughout all disease spectrums; however, the precise prevalence is underestimated due to the lack of standardized evaluation tools, especially in children [38] . A previous NHS found that 52% of the ACTA1 and 57% of the NEB patients presented bulbar weakness [5] , highlighting how frequent and important this feature is across this patient population.…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
“…The formal evaluation of bulbar weakness is challenging. Early signs such as weak cough, failure to thrive, difficulty to gain weight and long meal duration are often discreet and can be masked by other symptoms [38] . There is no validated clinical assessment for evaluating bulbar weakness in congenital myopathies, but tests validated for other neuromuscular diseases like the SLURP test 39] , the Sidney Swallowing Questionnaire (SSQ), [40] and the Neuromuscular Disease Swallowing Status Scale (NdSSS) [41] may be helpful in assessing patients with NM as well.…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%